Effectiveness and Safety of Immunosuppressive Drug Therapy for Neuromyelitis Optica Spectrum Disorders: An Overview of Meta-Analyses and Systematic Reviews - Luo, Yuan; Deng, Yuqian; Ran, Haiye; Yu, Lei; Ma, Caili; Zhao, Liping; Li, Yunchen (Current Neuropharmacology, 2023)
Objective: This study aims to provide an overview of meta-analyses and systematic reviews on the effectiveness and safety of immunosuppressive drug therapy for neuromyelitis optica spectrum disorders (NMOSD) by evaluating the methodological quality and reporting quality of reviews. Methods: The Chinese National Knowledge Infrastructure (CNKI), WanFang Data, China Science and Technology Journal Database, Web of Science, the Cochrane Library, PubMed, and Embase databases were searched to collect systematic reviews or meta-analyses on the effectiveness and safety of immunosuppressive therapy for NMOSD from inception to December 2, 2021. Two researchers independently screened reviews and extracted data. Any differences in the procession of review assessment between the two researchers were re-evaluated, and the disagreement was resolved by discussion with other researchers. The following data were extracted: author, year of publication, the country where the study was conducted, study type, the number of included studies, sample size, risk bias tools, medication of immunosuppressive therapy, and main outcomes. Then, the AMSTAR-2, which is a critical appraisal tool for systematic reviews (2nd edition), and Grades of Recommendation, Assessment, Development and Evaluation (GRADE) were used to evaluate the methodological quality and reporting quality of evidence. A comprehensive analysis was conducted on the outcomes for all included reviews. Results: A total of 15 reviews were included. Of the included reviews, 3 were systematic reviews, 7 were meta-analyses, and 5 were systematic reviews and meta-analyses. According to the AMSTAR-2 criteria, 6 studies had high quality, 1 study had moderate quality, 4 studies had low quality, and 4 studies had critically low quality. Based on the GRADE, neither evidence quality for effectiveness nor safety was high. Conclusion: Immunosuppressive drug therapy is effective for patients with NMOSD, but its safety is controversial. Due to the poor quality of evidence, reliability needs to be considered. Thus, large sample, multi-center, double-blind, randomized controlled studies are still needed in the future.
Keywords: GRADE